Bodies of maize, eaters of grain : comparing material worlds, metaphor and the agency of art in the Preclassic Maya and Mycenaean early civilisations /: comparing material worlds, metaphor and the agency of art in the Preclassic Maya and Mycenaean early civilisations. (2017) - Bajema, Marcus Jan, 1979-
No abstract available